Comprehensive study on limestone weathering grade and risk potential in Batu Caves, Malaysia - Nik Daud, Nik Norsyahariati; Hamasa, Kambakhsh (The Journal of The Institution of Engineers, Malaysia, 2023)
The limestone formations within Batu Caves, situated in the Selangor region, represent a significant geological phenomenon in Malaysia, capturing the attention of engineers due to their distinctive karst features. The assessment entails a comprehensive review of geological characteristics, currently employed categorization frameworks, assessment approaches, and the possible ramifications for the construction industry, infrastructure advancement, and the natural surroundings. This study aims to enhance the collective comprehension of limestone weathering and its impact on risk assessment due to weathered processes. The insights gained from the distinctive circumstances surrounding Batu Caves possess the capacity to guide optimal approaches and tactics for addressing the consequences of limestone weathering. The Batu Caves attracts a substantial number of tourists annually. Consequently, it is subject to significant levels of human activity and encounters high traffic volumes. Moreover, Batu Caves encompasses an assemblage of Hindu temples and shrines, setting it apart from numerous other limestone formations due to its cultural and religious significance. The impact of urban environments on weathering processes differs significantly from that observed in limestone formations found in other geographical areas. Based on the geological landscape of Batu Caves, effects reveal moderate stability in sections 1, 3, and 8, while sections 6 and 7 pose an elevated risk of limestone collapse. These sections have lost their stability due to weathering activity and require an emphasis on effective risk-reduction measures to preserve the cave. The parts assessed as risk areas need risk reduction techniques such as taking nets, giving solid foundations, and installing danger signs to protect people who come to the area. This analysis provides a deeper understanding of limestone weathering in Batu Caves, emphasizing the need for efficient risk mitigation techniques to address weathering issues. This could lead to preserving Batu Cave's geological significance and potentially global applications for limestone-rich places. The study contributes to engineering, construction, and environmental conservation by providing valuable resources for decision-making.